Analysis of the expression of nine secreted matrix metalloproteinases and their endogenous inhibitors in the brain of mice subjected to ischaemic stroke - Lenglet, Sébastien; Montecucco, Fabrizio; Mach, François; Schaller, Karl; Gasche, Yvan; Copin, Jean-Christophe (Thrombosis and Haemostasis, 2014)
Matrix metalloproteinases (MMPs) are a family of more than twenty secreted and cell-surface endopeptidases. Among them, MMP2, MMP3 and MMP9 are involved in blood-brain barrier injury and neuronal death after cerebral ischaemia. On the other hand, very little is known about the expression of the other secreted MMPs. Herein, we compared the global changes in MMP1, MMP2, MMP3, MMP7, MMP8, MMP9, MMP10, MMP12 and MMP13, and their endogenous inhibitors TIMP1 and TIMP2, both at the mRNA and protein levels, during the hyperacute (6 h), acute (24 h) and subacute (72 h) stages following transient focal cerebral ischaemia and treatment with recombinant tissue plasminogen activator (rtPA). We observed a significant increase in MMP1, MMP2, MMP9, MMP10, MMP13 and TIMP1 levels during the acute stage of reperfusion, which was further amplified during the subacute stage for MMP1, MMP2, MMP10 and TIMP1. In general, no change of MMP3, MMP7, MMP8, MMP12 and TIMP2 was observed. However, rtPA treatment induced a rapid increase in MMP1/TIMP2, MMP2/TIMP2, MMP8/TIMP2 and MMP9/TIMP2 ratios during the hyperacute stage of reperfusion compared to saline treatment, which may have potential implications in the early disruption of the blood-brain barrier after rtPA treatment.
Keywords: Brain ischaemia; MMP; TIMP; tPA; animal model